Prevalence of frailty syndrome and its associated factors among community-dwelling older adults in Kuala Nerus, Terengganu, Malaysia - Mohd Hamidin, Fairus Asma (2017)
Frailty syndrome is a clinical syndrome that decreases resistance to stressors, resulting from cumulative declines across multiple physiological systems. It is closely related to ageing which increases the risk of falls, hospitalisation, disability and death. In Malaysia, the data on frailty syndrome are still limited and less studied. A cross-sectional study on 279 community-dwelling older adults (118 male and 161 female) aged 60 years and above was conducted in four sub-districts (Seberang Takir, Tepoh, Wakaf Tembusu, and Bukit Tunggal) in Kuala Nerus to determine the prevalence of frailty syndrome and its associated factors. This study assessed the frailty syndrome through quantitative measurement based on the “phenotype of frailty” defined by Fried et al., (2001) that has been validated in the Cardiovascular Health Study. Respondents were classified as non-frail (score: 0-2) or frail (score ≥ 3). The characteristics of the respondents were assessed through the structured questionnaire which consisted of sociodemographic and socioeconomic characteristics, health-related status, dietary intake, and anthropometric measurements including body mass index, body circumference and body composition. The prevalence of frailty syndrome among the respondents was 18.3%. The mean age of respondents was 73.32 (S.D = 6.10) years with 60.2% in age 60-74 years. Majority of the respondents were living with others (82.4%), unemployed (83.5%) and depended on others for monetary support (78.5%). About 13.3% of the respondents were obese and 9.3% were underweight. The average daily energy intake for male and female were 1163 + 294 kcal and 966 + 291 kcal, respectively, which are both below the Recommended Nutrient Intake (RNI). In the bivariate analysis, the factors associated with frailty syndrome included: advanced age, unmarried, no formal education, unemployed, poor hearing, appetite loss, hospitalisation in the previous year, poor self-rated health, lower body mass index, lower waist circumference, lower mid-upper arm circumference, lower calf circumference, lower percentage of total body fat and lower lean body mass. After a multivariate analysis through binary logistic regression, advanced age [odds ratio (OR): 3.29; 95% confidence interval (CI): 1.41 – 7.69], unmarried [OR: 4.25; 95% CI: 1.68 – 10.75], hospitalisation in the previous year [OR: 4.38; 95% CI: 1.50 – 12.79], poor self-rated health [OR: 4.73; 95% CI: 2.04 – 10.99], and lower body mass index [OR: 0.88; 95% CI: 0.80 – 0.98] were significantly associated with frailty syndrome. The characteristics of frail older adults and the factors associated provide an overview on underlying effects and guiding actions for prevention programs functioning to reverse and minimize the adverse effects of frailty syndrome.